2009
DOI: 10.2319/092908-509r.1
|View full text |Cite
|
Sign up to set email alerts
|

Face and Neck Dermatitis from a Stainless Steel Orthodontic Appliance

Abstract: Although nickel is the most common cause of contact allergy, nickel-containing orthodontic appliances seldom cause adverse reactions that result in discontinuation of treatment. We report on an eruption of dermatitis in the face and neck of an adult female patient after placement of a rapid maxillary expansion appliance (RME). Because the patient suspected nickel allergy, her tolerance to the appliance material was tested intraorally before treatment by cementing bands on four teeth for a week. No visible adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
1
13
0
8
Order By: Relevance
“…They also reported a higher prevalence of nickel allergy in girls, which is also reported in other papers [56,57]. Although orthodontic alloys are considered safe, there are case reports on nickel hypersensitivity caused by orthodontic appliances, both from stainless steel and nickel-titanium alloys [50,[58][59][60]. Common intra-oral signs include redness, swelling, and soreness of the oral mucosa and palate, gingiva and lips [59].…”
Section: Corrosion and Elemental Releasesupporting
confidence: 59%
See 1 more Smart Citation
“…They also reported a higher prevalence of nickel allergy in girls, which is also reported in other papers [56,57]. Although orthodontic alloys are considered safe, there are case reports on nickel hypersensitivity caused by orthodontic appliances, both from stainless steel and nickel-titanium alloys [50,[58][59][60]. Common intra-oral signs include redness, swelling, and soreness of the oral mucosa and palate, gingiva and lips [59].…”
Section: Corrosion and Elemental Releasesupporting
confidence: 59%
“…Common intra-oral signs include redness, swelling, and soreness of the oral mucosa and palate, gingiva and lips [59]. Extra-oral manifestations, such as dermatitis, may also be observed [58].…”
Section: Corrosion and Elemental Releasementioning
confidence: 99%
“…Case reports of allergic reactions during orthodontic therapy support this suspect [11,26]. Moreover, in-vitro evidence indicates that Ni can cause cytotoxic, immunogenic, mutagenic or carcinogenic processes in dependence on the chemical form, concentration, duration and route of exposure [9,14,18,30,47].…”
Section: Resultsmentioning
confidence: 99%
“…A "safety threshold" of Ni release without biological repercussions has not been considered up to now. Furthermore, it has been reported that in cases of hypersensitivity to orthodontic appliances, removal of the appliances clearly results in an improvement in the symptoms [28,[47][48][49]. At the cellular level, other studies have reported that Ni-containing orthodontic appliances may induce DNA damage [32] or increase epithelial cell proliferation [50].…”
Section: Discussionmentioning
confidence: 98%